PRECISION AND STABILITY OF THE PREDICTION FORMULA FOR BURST STRENGTH OF PRESSURE-BEARING CYLINDER - LIU Cen; YANG Fan; WU SengLin; HONG Kai; ZHANG Shu; LIU XiaoNing (Jixie qiangdu)
To provide a basis for selecting formulas or extending their applied ranges,applying probability theory and mathematical statistics,a comparison and evaluation method of formula stability and precision was established. Based on the study that the ratio of actual burst pressure to the formula calculated value was basically in accordance with the normal distribution random variables, comparing and evaluation the formula stability from the variation coefficient of distribution parameters fluctuation range,comparing and evaluation the formula precision from the distribution parameters value interval contact ratio.When the bilateral confidence was 98% and in the applied range of the formula,the stability and precision of Mid-diameter formula,Tresca formula,Faupel formula and Rheological stress formula were compared and evaluated. The researching results shown that:（ 1） It is the basic conditions for selecting formulas or extending their applied ranges that stability and precision not reduced.（ 2） For pressure-bearing single-layer cylinder,the applied range of the Mid-diameter formula for measured burst pressure specified by the standard,it can be extended from no more than 105 MPa to no more than 329. 6 MPa,the stability of the Mid-diameter formula is obviously improved and the precision is not reduced. The applied range of the Tresca formula for measured burst pressure specified by the standard,it can be extended from between 91. 0 MPa and 300 MPa to no more than329. 6 MPa,the stability of the Tresca formula is obviously improved and the precision is not reduced. If the measured burst pressure was not exceed 329. 6 MPa,the stability and precision is no significant difference between the Mid-diameter formula and the Tresca formula. When the applied range of the Rheological stress formula for measured burst pressure was not less than 220 MPa,and the applied range of the Faupel formula for measured burst pressure was not less than 250 MPa,the precision of the two formulas is not significantly different,and the stability of Rheological stress formula is obviously better than Faupel formula.For Mid-diameter or Tresca formula with measured burst pressure not exceeding 329. 6 MPa,and for Rheological stress formula with measured burst pressure not less than 220 MPa,the stability of Mid-diameter or Tresca formula is obviously better than the Rheological stress formula,and the precision is higher than the Rheological stress formula.（ 3） For flat steel ribbon wound pressure vessel with measured burst pressure was not exceed 209. 7 MPa,the precision and stability of Mid-diameter formula is lower than that of four predictor formulas of burst pressure for pressure-bearing single-layer cylinder.